2013
DOI: 10.1016/j.intimp.2013.02.007
|View full text |Cite
|
Sign up to set email alerts
|

CTLA4-Ig immunosuppressive activity at the level of dendritic cell/T cell crosstalk

Abstract: Immunosuppressive cytotoxic T lymphocyte associated antigen-4 immunoglobulin fusion proteins (CTLA4-Ig) block the CD28:CD80/86 costimulatory pathway. On a cellular level, CTLA4-Ig is understood to dampen T cell responses. As a mechanism, CTLA4-Ig has been reported to affect dendritic cell (DC) function via inducing the immunosuppressive indoleamine 2,3 dioxygenase (IDO) pathway and promoting a DC regulatory phenotype. We here probed cellular mechanisms of CTLA4-Ig immunoregulation in an allogeneic setting usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 43 publications
(31 reference statements)
2
27
0
Order By: Relevance
“…Consistent with our recent observation (19), using C57BL/6-derived bone marrowYderived dendritic cell (BMDC) as stimulators of allogeneic Balb/c T cells, we first showed that CTLA4-Ig (100 Kg/mL) potently inhibited the allogeneic T-cell proliferative response (Fig. 1A).…”
Section: Ctla4-ig Enhances the Proportion Of T Cells With A Regulatorsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with our recent observation (19), using C57BL/6-derived bone marrowYderived dendritic cell (BMDC) as stimulators of allogeneic Balb/c T cells, we first showed that CTLA4-Ig (100 Kg/mL) potently inhibited the allogeneic T-cell proliferative response (Fig. 1A).…”
Section: Ctla4-ig Enhances the Proportion Of T Cells With A Regulatorsupporting
confidence: 90%
“…CTLA4-Ig mainly exerts its inhibitory action by interfering with costimulatory signals that are necessary for T-cell activation (19). In addition to that, recent studies report that CTLA4-Ig might further promote inhibition by inducing allospecific deletion by apoptosis (25).…”
Section: Ctla4-ig Shows Reduced Apoptosis In T Regsmentioning
confidence: 99%
See 1 more Smart Citation
“…6C). Since cytotoxic T lymphocyte-associated antigen-4 (CTLA-4) expressed by Treg cells could affect DC function via inducing IDO pathway and promoting a DC regulatory phenotype in vivo[35], we suggest that this phenomenon is associated with the existence of newly induced DC with high IDO activity caused by induced Foxp3 + Treg cells. Therefore,the induced Treg cells in turn induced tolerant DC and IDO, composing a loop, maintaining a lasting tolerant state in transplanted mice.…”
mentioning
confidence: 96%
“…cell line, Raji cell was grown in RPMI 1640 supplemented with 10 % FBS. Meanwhile, splenic DCs from BALB/c mice were prepared following previously described protocols [24]. In brief, spleens were injected with type IV collagenase and processed with 400 unit/mL type IV collagenase solution for 30 min at 37°C to prepare single cell suspensions.…”
Section: B-cell-targeting Assaymentioning
confidence: 99%